Implementation of Sustainable Development Law on the Empowerment of Coastal Communities in Supporting Food Security: A Study on Coastal Communities in Malauku - Hanarko Djodi Pamungkas; Hambali Thalib; La Ode Husen; Muh. Zulkifli Muhdar (Al-Ishlah: Jurnal Ilmiah Hukum, 2026)
This study examines the implementation of sustainable development law in empowering coastal communities to support food security in the waters of Maluku. The research is grounded in the understanding that sustainable development integrates economic, social, and environmental dimensions within a legal framework to ensure justice, legal certainty, and societal welfare. Coastal communities in Maluku possess significant marine resource potential; however, they continue to face structural challenges such as limited access to capital, low technological capacity, and inadequate market integration. This study employs an empirical legal research method with a socio-legal approach, combining normative legal analysis and field data obtained through interviews and literature review. The findings reveal that the implementation of sustainable development law has a strategic role in improving community welfare and strengthening food security through fisheries-based resources. Nevertheless, its effectiveness is influenced by multidimensional factors, including regulatory clarity, institutional capacity, community participation, access to resources, and the integration of local socio-cultural values such as sasi laut. The study also highlights the importance of synergy between government institutions, communities, and other stakeholders in ensuring the sustainability of empowerment programs. Strengthening regulatory harmonization, institutional capacity, access to financing and technology, and participatory approaches based on local wisdom are essential to enhance policy effectiveness. Furthermore, consistent law enforcement and improved monitoring and evaluation systems are necessary to maintain the sustainability of marine resources. This study contributes both theoretically and practically by providing insights for policymakers in developing more inclusive, adaptive, and sustainable coastal development strategies